Determinants of house affordability Kota Kinabalu / Azlan Mohd Hanif - Mohd Hanif, Azlan (2014)
This study is focused on to determine the determinants of house affordability in Kota Kinabalu, Sabah whether income, house price and housing loan are related to the house affordability. This empirical study focuses on 228 respondents who are working in several sectors. Using the survey approach, the findings showed that housing loan has a significant relationship with house affordability in Kota Kinabalu. The findings of this paper will provide important and additional information for the financial institutions to loosening the housing loan requirements for the applicants in order to people can own a house especially the first home buyers.